Prospective Role of Peptide-Based Antiviral Therapy Against the Main Protease of SARS-CoV-2 - Mahmud, Shafi; Paul, Gobindo Kumar; Biswas, Suvro; Afrose, Shamima; Mita, Mohasana Akter; Hasan, Md. Robiul; Shimu, Mst. Sharmin Sultana; Hossain, Alomgir; Promi, Maria Meha; Ema, Fahmida Khan; Chidambaram, Kumarappan; Chandrasekaran, Balakumar; et al. (Frontiers in Molecular Biosciences, 2021)
The recently emerged coronavirus (SARS-CoV-2) has created a crisis in world health and economic sectors as an effective treatment or vaccine candidates are still developing. Besides, negative results in clinical trials and effective cheap solution against this deadly virus has brought new challenges. The viral protein, the main protease from SARS-CoV-2, can be effectively targeted due to its viral replication and pathogenesis role. In this study, we have enlisted 88 peptides from the AVPdb database. The peptide molecules were modeled to carry out the docking interactions. The four peptides molecules, P14, P39, P41, and P74, had more binding energy than the rest of the peptides in multiple docking programs. Interestingly, the active points of the main protease from SARS-CoV-2, Cys145, Leu141, Ser139, Phe140, Leu167, and Gln189, showed non bonded interaction with the peptide molecules. The molecular dynamics simulation study was carried out for 200ns to find out the docked complex's stability where their stability index was proved to be positive compared to the Apo and control complex. Our computational works based on peptide molecules may aid the future development of therapeutic options against SARS-CoV-2.